Re-evaluation of Rural Development Problematic in the Context of Social Capital* - Ayşe Nur ÖKTEN; Tuba İNAL ÇEKİÇ (Megaron, 2009)
The matter of “rural development” has been an important issue for approximately 20 years. International organizations like the United Nations, the World Bank and the European Union, as well as many developed and developing countries are devoting increasing time and resources to the rural development issue. Studies in economics, politics and geography, on the other hand, lay out the theoretical framework in this matter. Rural poverty, migration to urban areas, pollution of water and agricultural land, problems of agricultural production, and introducing global solutions to these problems have become primary issues on the agendas of many countries. The aim of the paper is to discuss the rural development policies with built-in global solutions in a new perspective, in the context of local social structure and relations. Accordingly, the paper addresses the change in the rural development paradigm and the role of social capital in rural development.